The importance of the instrumental factor and its role in translation a text from Russian to Arabic and Arabic to Russian - Shahadha, Abbas Abdulameer (lark, 2019)
Abstract: The research focuses on the concept of instrumentalism and what it means in linguistics, it is not limited to the concept of meanings of the units or symbols of the language, but addresses all the issues related to the understanding of participants in the process of communication, and addresses the treatment of these issues according to the experience of people language and non-language, which surrounds the process of linguistic communication, And attitudes and contributors to verbal action, and dealt with the role of a successful translator who can be familiar with all issues related to the understanding of participants, which include text, context and denominator.